2015
DOI: 10.1002/mus.24715
|View full text |Cite
|
Sign up to set email alerts
|

Whole plantar nerve conduction study with disposable strip electrodes

Abstract: The higher mean amplitude of whole plantar CNAPs obtained by our method suggests that it enables CNAPs to be obtained easily, even in elderly people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Some authors suggest that the study of fibers even more distal than the sural, such as the fibers of the plantar nerve, could be an early detector of diabetic neuropathy [ 129 , 130 , 131 , 132 ]. Others highlight how the joint study of peripheral nerves together, medial plantar and peroneal, in addition to dorsal sural NCS, could increase sensitivity in the detection of neuropathy, thus allowing earlier diagnosis, especially when routine NCS are normal [ 129 , 133 ].…”
Section: Diagnosismentioning
confidence: 99%
“…Some authors suggest that the study of fibers even more distal than the sural, such as the fibers of the plantar nerve, could be an early detector of diabetic neuropathy [ 129 , 130 , 131 , 132 ]. Others highlight how the joint study of peripheral nerves together, medial plantar and peroneal, in addition to dorsal sural NCS, could increase sensitivity in the detection of neuropathy, thus allowing earlier diagnosis, especially when routine NCS are normal [ 129 , 133 ].…”
Section: Diagnosismentioning
confidence: 99%
“…Our recent study has shown the clinical utility of orthodromic nerve conduction by using SSEs for evaluation of the whole plantar nerve (Hemmi et al, 2016). Since whole-nerve action potentials arising from a large number of terminal branches could be elicited at the same time by placement of SSEs, the highest amplitude was constantly obtained by our method, even in elderly people.…”
Section: Discussionmentioning
confidence: 94%
“…Since the feet are most commonly affected in length-dependent neuropathy, NCS of the more distal plantar nerves is more sensitive as an indicator of neuropathy than are sural studies ( 16 - 19 ). However, the small amplitude evoked response and difficult NCS procedure have limited the routine use of medial or lateral plantar NCS ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since the feet are most commonly affected in length-dependent neuropathy, NCS of the more distal plantar nerves is more sensitive as an indicator of neuropathy than are sural studies ( 16 - 19 ). However, the small amplitude evoked response and difficult NCS procedure have limited the routine use of medial or lateral plantar NCS ( 19 ). Since we aimed to make the DPN index simple and easy to use and since both low amplitude SNAPs and slow SCVs in the sural nerve are major findings in DPN ( 20 ), we used the sural nerve instead of the medial or lateral plantar nerve for the analysis.…”
Section: Discussionmentioning
confidence: 99%